The Effectiveness of Essential Oils as Vegetable Pheromones Against Cocoa Pests Using The Trap Method - Eka Wahyuningsih; Ovy Erfandari; Hamdani (Jurusan Budidaya Perkebunan, 2024)
Cocoa plants are one of the important commodities in plantation crops. The decreasing cocoa production is caused by several factors, one of which is pest attacks. There are several main pests in cocoa plants, namely, fruit borer pests, fruit sucking pests and lice. Currently, the use of chemical insecticides has been widely studied, causing many residues that can pollute the environment and disrupt the stability of the agro-ecosystem. One alternative that can be used is the use of attractants, namely pheromones derived from plant extracts containing essential oils. The use of pheromones with the trap method is one of the insect trapping techniques that has been widely used in control. The purpose of this study was to obtain the best combination of essential oils as vegetable pheromones to control pests in cocoa plants. This study consisted of six treatments and three replications. Treatment consists of use of vegetable pheromones derived from patchouli oil, cinnamon oil, oil nutmeg, clove oil, control (water) and combination (all treatments).